Preparation of Monodisperse Poly(Methyl Methacrylate)/Polystyrene Composite Particles by Seeded Emulsion Polymerization Using a Sequential Flow Process - Watanabe, Takaichi; Karita, Kengo; Manabe, Midori; Ono, Tsutomu (Frontiers in Chemical Engineering, 2021)
We develop a sequential flow process for the production of monodisperse poly(methyl methacrylate)(PMMA)/polystyrene (PS) composite particles through a soap-free emulsion polymerization of methyl methacrylate (MMA) using the first water-in-oil (W/O) slug flow and a subsequent seeded emulsion polymerization of styrene (St) using the second W/O slug flow. In this process, monodisperse PMMA seed particles are first formed in the dispersed aqueous phase of the first W/O slug flow. Subsequently, removal of the oil phase from the slug flow is achieved through a porous hydrophobic tubing, resulting in a single flow of the aqueous phase containing the seed particles. The aqueous phase is then mixed with an oil phase containing St monomer to form the second W/O slug flow. Finally, monodisperse PMMA/PS composite particles are obtained by a seeded emulsion polymerization of St using the second W/O slug flow. We compared the reaction performance between the slug flow and the batch processes in terms of particle diameter, monomer conversion, particle size distribution, and the number of particles in the system. We found that internal circulation flow within the slugs can enhance mass transfer efficiency between them during polymerization, which results in monodisperse PMMA/PS composite particles with a large particle diameter and a high monomer conversion in a short reaction time, compared to those prepared using the batch process. We believe that this sequential microflow process can be a versatile strategy to continuously produce monodisperse composite particles or core-shell particles in a short reaction time.